Dose volume histogram constraints in patients with head and neck cancer treated with surgery and adjuvant HDR brachytherapy: A proposal of the head and neck and skin GEC ESTRO Working group. (January 2021) - García-Consuegra, Alejandro; Gimeno Morales, Marta; Cambeiro, Mauricio; Tagliaferri, Luca; Kovacs, Gyoergy; Van Limbergen, Erik; Ramos, Luis I.; Manuel Arnaiz, José; Alcalde, Juan; Lecanda, Fernando; Martinez-Monge, Rafael
Highlights: This study aimed to identify DVH Constraints of Osteonecrosis & SoftTissue Necrosis. The study evaluated 227 patients treated with surgery & HDR brachytherapy (+/- EBRT). Soft Tissue Necrosis correlated with CTVsize>15 cm 3 and Total EQD2-DVH TV100 > 87Gy. Osteoradionecrosis correlated with Physical Dose to Mandible 2cm 3  >61 Gy. Abstract: Background: The Head and Neck and Skin (HNS) Working group of the GEC-ESTRO acknowledges the lack of widely accepted Dose Volume Histogram (DVH) constraints in adjuvant head and neck brachytherapy and issues recommendations to minimize mandibular Osteoradionecrosis (ORN) and Soft Tissue Necrosis (STN). Methods: A total of 227 patients with the diagnosis of head and neck cancer treated with surgery and adjuvant HDR brachytherapy alone or combined with other treatment modalities during the period 2000–2018 were analyzed. Results: STN was observed in 28 out of 227 cases (12.3%) with an average time to appearance of 4.0 months. In previously unirradiated cases, there was a positive correlation between CTV size and STN ( p  = 0.017) and a trend towards significance between Total EQD2-DVH TV100 dose and STN ( p  = 0.06). The risk of STN in the absence of both factors (i.e, CTV < 15 cm 3 and Total EQD2-DVH TV100 dose < 87 Gy) was 2%, with one factor present 15.7% and with both factors 66.7% ( p  = 0.001). ORN was observed in 13 out of 227 cases (5.7%) with an average time to appearance of 26.2 months. In unirradiated cases, ORN correlated with Total Physical Dose to Mandible2cm3 ( p  = 0.027). Patients receiving Total Physical Doses greater than 61 Gy had a 20-fold increased risk of ORN. Conclusions: In Unirradiated patients the panel recommends to avoid implantation of postoperative CTVs exceeding 15 cm 3 at Total EQD2-DVH TV100 doses in excess of 87 Gy as well as to limit the irradiation of the Mandible2cm3 to 61 Gy. In previously irradiated patients the panel cannot make a recommendation based on the available results.